Vaginal atresia and cervical agenesis combined with asymmetric septate uterus: A case report of a new genital malformation and literature review. Issue 3 (January 2018) - Han, Tian-Tian; Chen, Juan; Wang, Shu; Zhu, Lan
Abstract: Rationale: A combination of Vaginal atresia and septate uterus as a novel genital malformation has been reported the first time. It offers a support for the bidirectional theory. Patient concerns: A 23-year-old woman presented with the inability to perform intercourse. The unprecedented variant was misdiagnosed by magnetic resonance imaging and ultrasonography as low vaginal atresia associated with complete septate uterus with functional endometrium in both the cavities. Diagnoses: The correct diagnosis was made and confirmed intraoperatively as a genital malformation, vaginal atresia and cervical agenesis associated with septate uterus. Intervention: laparoscopic and hysteroscopic diagnosis the novel malformation never been reported and a vaginal stent was recommended postoperatively. Outcomes: This rare clinical variant made misdiagnosis. Intraoperatively, unprecedented genital malformation was confirmed. There are no vaginal atresia cases in the literature with a septate functional uterus and single agenesis cervix. Lessons: Confirmed diagnosed by operation instead of depending on the imaging should be used for rare genital anomaly.